Therapeutic role of Wuda granule in gastrointestinal motility disorder through promoting gastrointestinal motility and decreasing inflammatory level - Jiang, Zhi; Zou, Qiuping; Chen, Qicheng; Zhang, Junhong; Tang, Hailin; Chen, Jingbao; Qin, You; Yang, Liming; Chen, Zhiqiang; Cao, Lixing (Frontiers in Pharmacology, 2023)
Previous studies indicated that Wuda Granule (WDG) has been applied in the treatment of gastrointestinal motility disorder (GMD), but the effect and underlying mechanisms is yet to be elucidated. This study aimed to explore the mechanism and pharmacological effect of WDG for GMD via network analysis, verification of animal experiments and clinical experiments. The results showed that 117 effective active compounds of WDG were screened and 494 targets of WDG compounds targeting GMD were selected. These targets were involved in the biological process of inflammatory regulation and the regulation of gastrointestinal motility. The mechanism was mainly involved in the regulation of PI3K-Akt signaling pathway and Rap1 signaling pathway. In addition, This is a provisional file, not the final typeset article molecular docking analysis suggested that 8 key active compounds of WDG may be mainly responsible for the effect of WDG on GMD by targeting HARS, AKT, and PIK3CA, respectively.Animal experiments and clinical trials both suggested that WDG could exert therapeutical effect on GMD via inhibiting inflammation and promoting gastrointestinal motility, it could also improve digestive function of patients with laparoscopic colorectal cancer after surgery. This study was the first to demonstrate that WDG improved GMD mainly via inhibiting inflammatory level and promoting gastrointestinal motility, providing new insights for the understanding of WDG for GMD, inspiration for future research and reference for clinical strategy in terms of the treatment of GMD.